Authenticity assessment of commercial bakery products with chia, flax and sesame seeds: Application of targeted and untargeted metabolomics results from seeds and lab-scale cookies. (October 2022) - Brigante, Federico I.; Lucini Mas, Agustin; Erban, Alexander; Fehrle, Ines; Martinez-Seidel, Federico; Kopka, Joachim; Wunderlin, Daniel A.; Baroni, Maria V.
Abstract: Usually the investigations in food authenticity focus on the discovery of new markers in laboratory-made products. However, tests in commercial products are indispensable yet rarely performed. This work presents the application of the discovered markers of chia, flax and sesame seeds in two previous studies carried out by HPLC-MS/MS and GC-MS. A set of commercial bakery products was analyzed by the same workflows to assess their authenticity regarding the declaration of the seeds in the ingredients list and the package. Presence or absence of the seeds was determined by evaluation of the corresponding markers in the products. All the bakery products passed the evaluation process and were declared as authentic by both analytical techniques. Markers coming from both techniques for each of the seeds were complementary since using them as groups represents a major advantage when studying food adulteration. Highlights: Authentication of commercial products is required when proposing new markers. Seeds in commercial baked goods were authenticated through proposed markers. Even when other seeds were added, chia, flax, and sesame seeds could be identified. Better authentication results can be obtained with combination of targeted and untargeted techniques.